KEPASTIAN HUKUM PEMBENTUKAN BADAN BANK TANAH PASCA PUTUSAN MAHKAMAH KONSTITUSI - Eka Muji Diliwiyana (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The state through government agencies or independent institutions appointed by the government has the authority to acquire abandoned land, manage and regulate it temporarily, distribute it in the public interest. This is a land policy called the Land Bank. In this study, the type of research used is normative legal research. The legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials is done by literature study. The technique of analyzing legal materials is carried out using descriptive and normative methods. The results showed that the Land Bank is one of the important resource management tools to increase the productivity of land use. The methods used in the land bank are market control and local market land stabilization. The philosophical and juridical basis for the establishment of a land bank agency is that the state has an obligation to fulfill the basic rights of its citizens such as work, a decent living, a place to live, a source of food to an adequate environment, this is in line with the provisions contained in the preamble and Article 33 of the 1945 Constitution of the Republic of Indonesia. Legal certainty for the establishment of the Land Bank Agency after the Constitutional Court's Decision is the issuance of Government Regulation Number 64 of 2021 concerning the Land Bank Agency.